TRANSFORMATIONAL LEADERSHIP, WORK PRODUCTIVITY, INNOVATIVE BEHAVIOR MODERATE INDIVIDUAL CHARACTERISTICS ON TEACHER PERFORMANCE - Cahyaningsih, Gita (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Teacher performance is an indicator of the Indonesian Education Report Card. An appropriate leadership model is needed to evaluate teacher performance in schools. Individual characteristics in self-development also play an important role in work productivity. Innovative teachers become examples for students in creative thinking. The research uses quantitative methods. The research population was state elementary school teachers in East Jakarta. The sample selection method was purposive sampling with a total of 210 respondents. Data collection through testing questionnaires using SEM PLS. Test result transformational leadership t value of 5,743, work productivity t value of 2,051, innovative behaviour The t value is 10.813 and individual characteristics as a moderating variable have a t value of 0.771. 1. Transformational leadership has a positive impact on teacher performance. 2. Work productivity has a positive impact on teacher performance. 3. Innovative Behavior has a positive impact on teacher performance. 4. Individual characteristics are not able to strengthen the influence of work productivity variables on performance.